Subsurface geology of the Torino metropolitan area (Westernmost Po Plain, NW Italy) - Andrea Irace; Igor Marcelli; Gianfranco Fioraso; Andrea Festa; Rita Catanzariti; Brunella Raco; Matia Menichini; Giulio Masetti; Elisa Brussolo; Gianna Vivaldo; Marco Doveri (Journal of Maps)
The 1:100,000 subsurface geological map of the Torino metropolitan area covers ∼900 km2 in the westernmost Po Plain, an area of great relevance being crossed by the late Neogene to Quaternary ‘Torino Hill Front’ (THF), a tens of kilometers long, NW-verging buried and blind thrust. The map provides an updated representation of the bedrock geology below the late Early Pleistocene-Holocene Alpine-sourced fluvial blanket, relying on novel correlation of shallow water well and borehole logs. The map describes how the syn-depositional thrust-related folding pulses affected the early Piacenzian-early Middle Pleistocene tectono-stratigraphic evolution of this sector. Our results demonstrate that the deposition of the lower Piacenzian shallow marine succession and then of the Piacenzian to Calabrian alluvial record was controlled by the stepwise propagation of the THF, and suggest that this thrust was apparently sealed by the late Early Pleistocene unconformity. Gentle folding characterized the late Early Pleistocene-early Middle Pleistocene time interval.